2016
DOI: 10.1080/00365521.2016.1250282
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric evaluation of a daily gastro-oesophageal reflux disease symptom measure

Abstract: Based on existing evidence, the HRDQ is a valid and reliable measure of GORD symptoms that can be used as a study outcome in clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Primary efficacy data were based on the HRDQ, a measure designed specifically to capture symptoms that are most relevant for patients with uncontrolled GERD symptoms while taking daily PPIs. The HRDQ was adapted from the two most extensively tested patient‐reported outcome measures, the RDQ and ReQuest questionnaires which, while well‐validated, are not designed for patients with residual GERD symptoms while on therapy.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Primary efficacy data were based on the HRDQ, a measure designed specifically to capture symptoms that are most relevant for patients with uncontrolled GERD symptoms while taking daily PPIs. The HRDQ was adapted from the two most extensively tested patient‐reported outcome measures, the RDQ and ReQuest questionnaires which, while well‐validated, are not designed for patients with residual GERD symptoms while on therapy.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies indicate that addition of alginate may help maintain symptom control at initiation of PPI treatment and when stepping down to a maintenance dose or discontinuing PPIs, a period when rebound acid hypersecretion can be problematic . The only published randomised clinical trial to investigate alginate (Gaviscon Advance) as add‐on therapy in patients with breakthrough symptoms demonstrated a reduction in reflux symptoms using the validated Heartburn Reflux Dyspepsia Questionnaire (HRDQ) daily recall patient questionnaire as the outcomes measure. This study reported absolute changes in HRDQ scores from baseline, with significantly greater reductions being observed for add‐on Gaviscon Advance vs placebo.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been successfully used first line for post-prandial heartburn, and as an add-on to PPI in refractory GERD 8 determined by HRDQ. 9 Coyle et al first reported an exploratory study that demonstrated superiority of Gaviscon DA over placebo in patients with continued frequent heartburn, an abnormal HRDQ score and compliance with once daily PPI. However, their larger, confirmatory study changed the scoring of the HRDQ for the primary outcome.…”
mentioning
confidence: 99%